PINK1 expression increases during brain development and stem cell differentiation, and affects the development of GFAP-positive astrocytes. Issue 1 (December 2016) - Choi, Insup; Choi, Dong-Joo; Yang, Haijie; Woo, Joo; Chang, Mi-Yoon; Kim, Joo; Sun, Woong; Park, Sang-Myun; Jou, Ilo; Lee, Sang-Hun; Joe, Eun-Hye
Abstract Background Mutation of PTEN-induced putative kinase 1 (PINK1) causes autosomal recessive early-onset Parkinson's disease (PD). Despite of its ubiquitous expression in brain, its roles in non-neuronal cells such as neural stem cells (NSCs) and astrocytes were poorly unknown. Results We show that PINK1 expression increases from embryonic day 12 to postnatal day 1 in mice, which represents the main period of brain development. PINK1 expression also increases during neural stem cell (NSC) differentiation. Interestingly, expression of GFAP (a marker of astrocytes) was lower in PINK1 knockout (KO) mouse brain lysates compared to wild-type (WT) lysates at postnatal days 1-8, whereas there was little difference in the expression of markers for other brain cell types (e.g., neurons and oligodendrocytes). Further experiments showed that PINK1-KO NSCs were defective in their differentiation to astrocytes, producing fewer GFAP-positive cells compared to WT NSCs. However, the KO and WT NSCs did not differ in their self-renewal capabilities or ability to differentiate to neurons and oligodendrocytes. Interestingly, during differentiation of KO NSCs there were no defects in mitochondrial function, and there were not changes in signaling molecules such as SMAD1/5/8, STAT3, and HES1 involved in differentiation of NSCs into astrocytes. In brain sections, GFAP-positive astrocytes were more sparsely distributed in the corpus callosum and substantia nigra of KO animals compared with WT. Conclusion Our study suggests that PINK1 deficiency causes defects in GFAP-positive astrogliogenesis during brain development and NSC differentiation, which may be a factor to increase risk for PD.